Common structural correlates of trait impulsiveness and perceptual reasoning in adolescence1. Issue 2 (11th November 2011) - Schilling, Christina; Kühn, Simone; Romanowski, Alexander; Banaschewski, Tobias; Barbot, Alexis; Barker, Gareth J.; Brühl, Rüdiger; Büchel, Christian; Charlet, Katrin; Conrod, Patricia J.; Czech, Katharina; Dalley, Jeff W.; et al.
Abstract Background: Trait impulsiveness is a potential factor that predicts both substance use and certain psychiatric disorders. This study investigates whether there are common structural cerebral correlates of trait impulsiveness and cognitive functioning in a large sample of healthy adolescents from the IMAGEN project. Methods: Clusters of gray matter (GM) volume associated with trait impulsiveness, Cloningers' revised temperament, and character inventory impulsiveness (TCI‐R‐I) were identified in a whole brain analysis using optimized voxel‐based morphometry in 115 healthy 14‐year‐olds. The clusters were tested for correlations with performance on the nonverbal tests (Block Design, BD; Matrix Reasoning, MT) of the Wechsler Scale of Intelligence for Children IV reflecting perceptual reasoning. Results: Cloningers' impulsiveness (TCI‐R‐I) score was significantly inversely associated with GM volume in left orbitofrontal cortex (OFC). Frontal clusters found were positively correlated with performance in perceptual reasoning tasks (Bonferroni corrected). No significant correlations between TCI‐R‐I and perceptual reasoning were observed. Conclusions: The neural correlate of trait impulsiveness in the OFC matches an area where brain function has previously been related to inhibitory control. Additionally, orbitofrontal GM volume was associated with scores for perceptual reasoning. The data show for the first time structural correlates of both cognitive functioning and impulsiveness in healthy adolescent subjects. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.